Complex permeability studies of Ni-Co-Zn ferrites synthesized by an oxalate precursor method - Ghodake, J. S.; Kambale, R. C.; Kulkarni, S. D.; Sawant, S. R.; Suryavanshi, S. S. (Smart Materials & Structures, 2009)
Nanocrystalline Co-substituted Ni-Zn ferrites have been synthesized by employing a co-precipitation technique using oxalate precursors. The co-precipitated oxalates were decomposed in air at 650 degrees C for 1 h and the powder was sintered at 1000 degrees C. The phase formation of the sintered ferrite was confirmed by x-ray diffraction studies. The lattice parameter a (angstrom) increases with the addition of Co(2+) which is attributed to the large ionic size of Co(2+) (0.78 angstrom), which replaces Ni(2+) (0.74 angstrom). The crystallite size has been estimated by the Debye-Scherrer formula using the full width at half-maximum (FWHM) of the line broadening of the (311) reflection and it is found to be in the range of 25-28 nm. Also, with increasing cobalt content the magnetocrystalline anisotropy constant (K(1)) and magnetostriction constant (lambda(s)) increase, and the grain size decreases, hence the value of initial permeability mu(i) decreases. The saturation magnetization M(s) and magnetic moment (n(B)) do not show any significant variation for all compositions varying with the cobalt content.